Study of Mangrove Tourism Ecoliteracy Based on Local Communities in West Papua - Echletus Jefry Maximus Sawaki; Serafin Wisni Septiarti; Tristanti (ASANKA : Journal of Social Science and Education, 2026)
This study aims to analyze the level of ecoliteracy among local communities in managing mangrove tourism in Kampung Ramiki, Wasior District, Teluk Wondama Regency. This research employed a descriptive qualitative approach through field observations, in-depth interviews, and documentation to explore community knowledge, perceptions, participation, and conservation practices related to mangrove ecosystem management. The findings reveal that the local community has developed basic ecoliteracy through traditional ecological knowledge and local wisdom, reflected in their awareness of mangrove functions as coastal protection areas, habitats for marine biodiversity, and essential resources supporting community livelihoods. However, this ecological awareness has not been fully transformed into systematic education-based tourism management and sustainable economic practices. The study also found that mangrove tourism management remains informal, with limited institutional capacity, unequal community participation, and insufficient managerial assistance. Strengthening environmental education, community capacity, and collaborative tourism governance is therefore essential to improve sustainable mangrove tourism development. This study contributes to expanding the understanding of community-based ecoliteracy by highlighting the integration of local ecological knowledge and sustainable tourism management as a strategy for balancing environmental conservation and socio-economic benefits in coastal communities.